51.1k views
0 votes
Complete the table using the rule
2x - y = 4

x 3 4 5 25 34
y _ _ _ __ __

1 Answer

3 votes

Answer:

2

4

6

46

64

Explanation:

2x - y = 4

2(3) - y = 4

6 - y = 4

-y = 4 - 6

-y = -2

y = 2

2x - y = 4

2(4) - y = 4

8 - y = 4

-y = 4 - 8

-y = -4

y = 4

2x - y = 4

2(5) - y = 4

10 - y = 4

-y = 4 - 10

-y = -6

y = 6

2x - y = 4

2(25) - y = 4

50 - y = 4

-y = 4 - 50

-y = -46

y = 46

2x - y = 4

2(34) - y = 4

68 - y = 4

-y = 4 - 68

-y = -64

y = 64

User Kenogu Labz
by
5.2k points